Estratégias discursivas para a ruptura de paradigmas de gênero em livros infantis da Coleção Antiprincesas - Fumagalli, Desireè Ribas (2018)
This dissertation adopts as a theme the linguistic strategies of approach of the genre in the books antiprincesas. Therefore, it is structured from the collection antiprincesas, whose books spread a new look, which questions the traditional fairy tales and presents protagonists with real stories. The three works that make up the research corpus tell the life stories of Clarice Lispector, Frida Kahlo and Violeta Parra. From these works, we aim to map the relationship between discursive strategies and the new proposal of approach to gender expressed in books. The main methodological approach that supports the analysis of books is the critical perspective of discourse analysis, since this design allows linking the discourse with the relations of power and ideology. Therefore, the methodological framework is developed especially considering the three-dimensional perspective of the discourse proposed by Norman Fairclough (2001) and aspects of systemic-functional linguistics structured by Michael Halliday (1989). With regard to the theoretical basis, we conceive four central axes: communication, discourse, gender and children's literature. Communication is based on our research through the mediatization bias, that is, we assume the children's book as a media object from the conception of the media as a practice, inserted in the social context. We approach the discourse from the conception of social change, adopting it not only in its role of representation, but also in the construction of reality. Gender relations are based on the poststructuralist perspective, which conceives the genre beyond biological foundationalisms, but as something built and supported socially and discursively. And finally, children's literature is weighted as a field of social and educational activity and the children's book as a media object, subject to investigation in relation to discourse and gender. With regard to the research results, we highlight the existence of five main strategies that contribute to the breakdown of gender paradigms: the strategy of approaching the reality of the protagonists' lives; the strategy of disruption of expected gender performances for women; the strategy of dynamism and didacticism in reading; the strategy of approaching the protagonists throughout the books; and finally, the strategy of approximation between text and context. These mechanisms allow us to perceive the children's book as a media object that questions and presents new ways of signifying gender relations, also proposing new possibilities of representation, especially starting from the ideological investment and the hegemonic struggles present in the discourse.